Assessment of ventricular wall motion with focused echocardiography during cardiac arrest to predict survival - DENİZBAŞI ALTINOK, ARZU; AKOĞLU, HALDUN (KARE PUBL, 2016)
Objectives: Our primary goal is to investigate the hypothesis that in patients with a detectable ventricular wall motion (VWM) in cardiac ultrasonography (US) during cardiopulmonary resuscitation (CPR), survival rate is significantly more than in patients without VWM in US. Material and methods: In our prospective, single center study, 129 adult cardiac arrest (CA) patients were enrolled. Cardiac US according to Focus Assessed Transthoracic Echo (FATE) protocol was performed before CPR. Presence of VWM was recorded on forms along with demographic data, initial rhythm, CA location, presence of return of spontaneous circulation (ROSC) and time until ROSC was obtained. Results: 129 patients were included. ROSC was obtained in 56/77 (72.7%) patients with VWM and 3/52 (5.8%) patients without VWM which is statistically significant (p > 0.001). Presence of VWM is 95% (95% CI: 0.95-0.99) sensitive and 70% (95% CI: 0.58-0.80) specific for ROSC. 43/77 (55.8%) patients with VWM and 1 (1.9%) of 52 patients without VWM survived to hospital admission which was statistically significant (p < 0.001). Presence of VWM was 100% (95% CI: 0.87-1.00) sensitive and 54% (95% CI: 0.43 -0.64) specific for survival to hospital admission. Conclusion: No patient without VWM in US survived to hospital discharge. Only 3 had ROSC in emergency department and only 1 survived to hospital admission. This data suggests no patient without VWM before the onset of CPR survived to hospital discharge and this may be an indication to end resuscitative efforts early in these patients. Copyright (C) 2016 The Emergency Medicine Association of Turkey. Production and hosting by Elsevier B.V. on behalf of the Owner.
Keywords: Cardiopulmonary resuscitation; Ultrasonography; Echocardiography; Ventricular wall motion; RESUSCITATION OUTCOMES; LIFE-SUPPORT; EMERGENCY; SONOGRAPHY; CARE